Types and Distribution of Macroinvertebrates Stressed by Heavy Metals in Mangrove Forests - W. Budijastuti, R. Ambarwati, N. Ducha, F. Rachmadiarti, L. Lisdiana and K. Sahani (Nature Environment and Pollution Technology, 2023)
Heavy metals can decrease the number of species in nature. This research aims to determine the relationship between the type of macroinvertebrates stressed by heavy metals in the Wonorejo Mangrove Area, Surabaya, East Java. This type of research is observational. The determination of stations was done using the purposive random sampling method. Tests for Pb and Cd content were carried out using the AAS method. Nutrient content testing was carried out using the AAS and Kjeldahl methods. Data analysis was presented descriptively, and multivariate analysis was done using Principal Component Analysis (PCA). Based on the present research, it can be concluded that there are variations in the type and distribution of macroinvertebrates stressed by heavy metals in the mangrove area of Surabaya. Station 1 is dominated by Ocypode ryderi, Station 2 by Assiminea sp., Station 3 by Scylla paramamosain, and Station 4 by Cerithidea sp. with the high presence of metals (Cd, Pb), and soil and water nutrients (Org-C, N) at Stations 1, 3, and 4. The Station 2 has only Pb. Assiminea sp. (Phylum Mollusca) can be the best candidate for metal bioindicators because it appears in all locations where soil and water have been contaminated with Pb and Cd metals without affecting their life.